Correlation Studies: The Relationship of Metacognitive Skills and Cognitive Learning Outcomes - Kusuma, Anindita SHM; Busyairi, Ahmad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Learning basic natural sciences is not only about understanding the universe, but also about developing the trained, critical and analytical thinking needed to succeed in various life contexts. Material in basic natural science learning often involves understanding complex concepts and abstract thought processes, so good metacognitive skills are needed in students. Well-developed metacognitive skills are very important so that students can understand basic concepts and principles well so that they are expected to have a significant correlation with student cognitive learning outcomes. The research uses correlational research methods. The variable relationship that will be looked at in the research is the relationship between metacognitive skills and students' cognitive learning outcomes in learning using the Reading Concept Mapping-Student Team Achievement Division (Remap-STAD) model. The subjects in this research were students who were taking basic natural science courses. Metacognitive skills are measured using an achievement test integrated with cognitive learning outcomes questions. The data analysis used in the research is correlation analysis and regression analysis. The research results show that there is a relationship between metacognitive skills and students' cognitive learning outcomes in learning using the Reading Concept-Student Team Achievement Divisions (ReMap-STAD) model. The correlation coefficient (r) value of metacognitive skills with cognitive learning outcomes is 0.945 (very high). The direction of the relationship between metacognitive skills and cognitive learning outcomes is a positive relationship. The coefficient of determination (r2) is 0.893, so it can be explained that the variability in students' cognitive learning outcomes is determined by 89.3% by metacognitive skills. The regression significance value proves that the regression line equation can be used for predictions. The regression line equation for the relationship between metacognitive skills and cognitive learning outcomes using the Reading Concept-Student Team Achievement Divisions (ReMap-STAD) model is =1.246+1.058X.